A multi-center prospective study of plant-based nutritional support in adult community-based patients at risk of disease-related malnutrition - Delsoglio, Marta; Griffen, Corbin; Syed, Rakshan; Cookson, Tobias; Saliba, Hanorah; Vowles, Amanda; Davies, Samuel; Willey, Nicola; Thomas, Jennifer; Millen, Nicola; Odeh, Nour; Longstaff, Jayne; et al. (Frontiers in Nutrition, 2023)
There is an emerging need for plant-based, vegan options for patients requiring nutritional support. Twenty-four adults at risk of malnutrition (age: 59 years (SD18); Sex: 18 female, 7 male; BMI: 19.0kg/m2 (SD3.3); multiple diagnoses) requiring plant based nutritional support participated in a multi-centre, prospective study of a (vegan suitable) multi-nutrient, ready-to-drink, oral nutritional supplement (ONS) (1.5kcal/ml; 300kcal, 12g protein/200ml bottle, mean prescription 275ml/day (SD115)) alongside dietary advice for 28 days. Compliance, anthropometry, malnutrition risk, dietary intake, appetite, acceptability, gastrointestinal (GI) tolerance, nutritional goal(s), and safety were assessed. Patients required a plant-based ONS due to personal preference/variety (33%), religious/cultural reasons (28%), veganism/reduce animal-derived consumption (17%), environmental/sustainability reasons (17%), and health reasons (5%). Compliance was 94% (SD16). High risk of malnutrition (‘MUST’ score ≥2) reduced from 20 to 16 patients (p=0.046). Body weight (+0.6kg (SD1.2), p=0.02), BMI (+0.2kg/m2 (SD0.5), p=0.03), total mean energy (+387kcal/day (SD416), p<0.0001) and protein intake (+14g/day (SD39), p=0.03), and the number of micronutrients meeting the UK reference nutrient intake (RNI) (7 vs. 14, p=0.008) significantly increased. Appetite (Simplified Nutritional Appetite Questionnaire (SNAQ) score; p=0.13) was maintained. Most GI symptoms were stable throughout the study (p>0.06) with no serious adverse events related. This study highlights that plant-based nutrition support using a vegan-suitable plant-based ONS is highly complied with, improving the nutritional outcomes of patients at risk of malnutrition.